Collaborative development of an educational resource on rehabilitation for people living with HIV. Issue 22 (23rd October 2018) - Solomon, Patricia; Salbach, Nancy M.; O'Brien, Kelly K.; Nixon, Stephanie; Worthington, Catherine; Baxter, Larry; Tattle, Stephen; Gervais, Nicole
Abstract: Objective: The objective of this study is to describe the collaborative development of a rehabilitation guide for people living with human immunodeficiency virus (HIV) which was adapted from an online resource for clinicians. Methods: We adapted a comprehensive evidence-informed online clinical resource for people living with HIV using a three-phase participatory process. In Phase 1, we interviewed 26 clinicians and 16 people living with HIV to gather recommendations on how to adapt and format the content to benefit people living with HIV. In Phase 2, we adapted the patient education resource using the recommendations that emerged from Phase 1. Phase 3 consisted of comprehensive stakeholder review of the revised resource on the adaptability, usability, communicability, and relevance of the information. Stakeholders participated in an interview to obtain in-depth information on their perspectives. Transcribed interviews underwent qualitative content analysis. Results: Stakeholders indicated that the e-guide had utility for people living with HIV, community HIV service organizations, and care providers. Conclusion: Engaging people living with HIV resulted in a more relevant and meaningful resource that incorporated patients' values, needs, and preferences. Implications : Involving multiple stakeholders and user groups in the adaptation and evaluation of online patient education resources can assist in meeting patients' needs through increasing the relevance, organization and presentation of the content, and incorporating patients' values and needs. Implications for Rehabilitation: Online patient education resources should be adapted in order to maximize relevance and meaningfulness to patients. Involving multiple stakeholders in the adaptation and evaluation of online patient education resources can assist in meeting patients' needs. Involving multiple stakeholders increases the relevance, organization and presentation of the content and allows the incorporation of patient values and needs. This collaborative approach with an emphasis on meaningful participation of patients and community may be of interest to others interested in promoting knowledge translation.